Tritium in the hydro-ecosystem of the South-Ukrainian Nuclear Power Plant - L. I. Grygorieva; А. O. Aleksieieva; O. V. Makarova (Ядерна фізика та енергетика)
Based on the results of radioecological studies in the aquatic ecosystem of the South-Ukrainian Nuclear Power Plant region (SUNPP), the tritium content in technological reservoirs (cooling pond, biological pond of the cleaning station, splash pool) and adjacent surface and groundwater bodies were analyzed. It is shown that the average annual volumetric activity of tritium in the water of technological reservoirs of the SUNPP during 2014 - 2018 is kept at the level of 110 - 160 Bq/l, with a tendency to increase with an average annual rate of 12 - 13 Bq/l, which correlates with a decrease in the volume of blowdown water discharge from the cooling pond (about 8698 thousand m3 per yr). Higher levels of volumetric activity of tritium were registered in the water of technical wells - leakage markers in the technical system, which, moreover, are fed from the pools of cooling towers and spray units. The tritium content in the bioponds of the sewage system of the SUNPP decreased from more than 1000 Bq/l in the early 1990s to 100 - 130 Bq/l in 2017 - 2018, which led to a decrease in its level in the Trikratsky reservoir and should affect lowering its level in groundwater sources, which are located below the natural runoff. Taking into account the physicochemical properties of tritium and the conclusions of well-known scientists about the extremely rapid accumulation of tritium in the environment, the necessity of hydroecological monitoring of the tritium content in surface water bodies is substantiated, the water of which is used for irrigation of agricultural crops and which are hydrodynamically connected with the technological water bodies of the SUNPP, as well as sources of drinking water located downstream of the natural runoff from the technological reservoirs of the nuclear power plant.